An estimation of the mesiodistal widths of unerupted permanent canines and premolars based on the sizes of erupted permanent mandibular incisors for Filipinos - Go, Susan Yang G.
The purpose of this investigation was to determine whether, with linear regression analysis based on cast measurements of mandibular incisor widths alone, a more accurate method than is now available for predicting the widths of unerupted canines and premolars of mixed dentition patients could be developed. Regression analyses were performed on data derived from 500 Filipino subjects (181 males and 319 females) from orthodontic practices in the Metro Manila area. Measurements were taken on plaster casts of the mandibular incisors, maxillary and mandibular canine, first premolars and second premolars. Regression equations were constructed for both sexes separately. A calculated estimation was also made using half the incisor widths plus a constant. The new equations and current prediction methods were tested on a separate validation sample of 200 Filipino subjects (100 males and 100 females). Results showed that the newly developed regression equations and calculated estimations are more accurate for predicting Filipino tooth sizes than the currently used Caucasian prediction equations of Moyers and that of Tanaka and Johnston.